Novel, concise and efficient protocol for non-natural piperidine compounds - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P. (RSC Advances, 2014)
Formal synthesis of L-altro-1-deoxynojirimycin, cis-3-hydroxypipecolic acid along with synthesis of (R)-piperidinol and a conceptually different advanced intermediate for non-natural piperidine alkaloids is reported from cis-butene-1,4-diol. The key reactions involved are Johnson-Claisen rearrangement, Sharpless asymmetric dihydroxylation, reductive lactamization and novel regioselective elimination.